Keanekaragaman Tumbuhan Berkhasiat Obat Pada Suku Noaulu Di Pulau Seram, Maluku - Sarmawaty Kotala; Nirmala Fitria Firdhausi (Biotropic : The Journal of Tropical Biology, 2019)
Noaulu an indigenous tribe of Seram Island who live in the Sepa Village of Amahai District, Maluku. This tribe still use forest products to fulfill their needs, including medication. Therefore, this study intends to know the kinds of medicinal plants used by the Noaulu Tribe and the types of diseases that can be treated. Collecting data in this study using survey method and an interview method with the public interest. Determination of the respondents was using purposive sampling method. Inventory of medicinal plants was done by a survey method survey based respondent information. The result of the research shows that there are 31 medicinal plants from 22 families. They are able to cure 20 diseases. The plants which are predominantly used are from Zingiberaceae family. Leaves of the plant are mostly used as the drugs.